Special brazing filler metal for tantalum / Q345R steel, preparation method and brazing process

By using AgCu eutectics as the matrix for tantalum/Q345R steel special brazing material, combined with the coordinated regulation of Ni, Sn, Ti, In, Ce and Ag2WO4, the brazing process is used to connect tantalum and Q345R steel, which solves the problems of complex explosion welding process, high cost and environmental damage, and achieves an efficient, economical and environmentally friendly connection effect.

CN119820177AActive Publication Date: 2025-04-15NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510252650.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-15
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

In the prior art, the connection between tantalum and Q345R steel adopts explosive welding process, which has problems such as complex process, high cost and great environmental damage.

Method used

The special brazing material for tantalum/Q345R steel with AgCu eutectic as the matrix is ​​used to coordinate the performance of AgCu eutectic by Ni, Sn, Ti, In, Ce and Ag2WO4, strengthen the plasticity of the brazing material and the bonding strength of the joint after welding, and connect by brazing process.

Benefits of technology

The efficient connection between tantalum and Q345R steel is achieved, reducing process complexity and cost, while reducing environmental damage, and improving mechanical properties and corrosion resistance after welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820177A_ABST
    Figure CN119820177A_ABST
Patent Text Reader

Abstract

The invention discloses special brazing filler metal for tantalum / Q345R steel. The brazing filler metal is composed of, by mass, 2%-5% of Ni, 2%-5% of Sn, 2%-5% of In, 1%-5% of Ti, 1%-2% of Ag2WO4, 0%-1% of Ce and the balance AgCu eutectic. The invention further discloses a preparation method and a brazing process of the special brazing filler metal for the tantalum / Q345R steel. According to the special brazing filler metal for the tantalum / Q345R steel, the AgCu eutectic serves as a matrix, the performance of the AgCu eutectic is cooperatively regulated and controlled through Ni, Sn, Ti, In, Ce and Ag2WO4, the plasticity of the brazing filler metal and the bonding strength of a tantalum / Q345R steel joint after welding can be enhanced, tantalum and the Q345R steel can be connected in a brazing mode, and the special brazing filler metal is suitable for connection of tantalum and the Q345R steel in the technical field of dissimilar material welding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding of dissimilar materials, and in particular relates to a special brazing filler metal for tantalum / Q345R steel, a preparation method and a brazing process. Background Art

[0002] As a special pressure-bearing equipment with potential leakage and explosion risks, pressure vessels are widely used and play an indispensable role in all fields of the national economy and national defense. With the rapid development of science and technology and the continuous innovation of industrial technology, the design, manufacturing and performance requirements of pressure vessels have reached an unprecedented level. In view of the high standards and strict requirements of pressure vessels in terms of pressure bearing capacity and sealing performance, the selection of suitable materials has become the key to ensure their safe and efficient operation. Among many materials, tantalum has gradually become the preferred material for the preparation of high-performance pressure vessels due to its unique physical and chemical properties.

[0003] Since the refining process of tantalum is complicated and the production cost is high, the cost can be reduced and the material structure can be lightweight by compounding dissimilar metals. Among them, Q345R steel is a widely used steel for pressure vessels, which has the characteristics of good weldability, high yield strength, good toughness, and good ductility. Its production technology and cost are relatively more economical and popular. In order to reduce costs and give full play to the performance advantages of tantalum and Q345R steel at the same time, compounding the two to achieve high-strength connection has become a potential research direction. At present, explosive welding is an effective solution for connecting tantalum and Q345R steel, but there are problems such as complex process, high cost, and great damage to the environment. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a special brazing material for tantalum / Q345R steel. The special brazing material for tantalum / Q345R steel uses AgCu eutectic as the matrix and uses Ni, Sn, Ti, In, Ce and Ag2WO4 to coordinately regulate the performance of AgCu eutectic, which can enhance the plasticity of the brazing material and the bonding strength of the tantalum / Q345R steel joint after welding, so that tantalum and Q345R steel can be connected by brazing, solving the problems of complicated explosion welding process, high cost and great environmental damage adopted in the prior art.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a special tantalum / Q345R steel solder, characterized in that the solder is composed of the following components in mass percentage: Ni 2%~5%, Sn2%~5%, In 2%~5%, Ti 1%~5%, Ag2WO4 1%~2%, Ce 0%~1%, and the balance is AgCu eutectic.

[0006] The present invention adopts AgCu eutectic as the matrix of the tantalum / Q345R steel special solder, and almost no intermetallic compound (IMC) is generated between the matrix and Ta and Fe elements, which is conducive to obtaining relatively excellent welding performance.

[0007] The present invention also discloses a method for preparing the above-mentioned tantalum / Q345R steel special brazing filler metal, which is characterized in that the preparation method comprises the following steps:

[0008] Step 1: adding Na2WO4 solution during the stirring process of AgNO4 solution to obtain a precipitate suspension;

[0009] Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder;

[0010] Step 3, the Ag2WO4 powder obtained in step 2 and the AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder and Ce powder are mixed with anhydrous ethanol and ultrasonically stirred, and then heated and stirred until the anhydrous ethanol is completely volatilized and then three-dimensionally shaken and mixed to obtain a composite powder;

[0011] Step 4: Put the composite powder obtained in step 3 into a mold and press it under a pressure of 50MPa to 150MPa, then heat it to 600°C to 700°C for primary vacuum sintering to obtain a primary sintered block;

[0012] Step 5: Pressing the primary sintered block obtained in step 4 under a pressure of 150 MPa to 300 MPa, and then heating to 600° C. to 700° C. for secondary vacuum sintering to obtain a secondary sintered block;

[0013] Step 6: Press the secondary sintered block obtained in step 5 under a pressure of 850 MPa or more, and then heat it to 550° C. to 650° C. for a third vacuum sintering to obtain a third sintered block;

[0014] Step seven, rolling the tertiary sintered block obtained in step six, then heating it to 600°C to 700°C and annealing it, repeating the process of first rolling and then annealing until the thickness of the tertiary sintered block is not more than 200 μm, and obtaining a special brazing material for tantalum / Q345R steel.

[0015] The present invention can promote the internal exhaust of the solder and improve the density of the solder by performing three pressing and sintering. Among them, the first pressing molding can ensure that the internal gas is fully discharged and natural shrinkage occurs by setting the pressure at 50MPa-150MPa; the second pressing molding sets the pressure at 150MPa-300MPa, while improving the density of the primary sintered block, the exhaust channel is still retained, so that the density of the primary sintered block is improved; the third pressing molding sets the pressure at more than 850MPa, further improving the density of the secondary sintered block and ensuring the subsequent processing performance; by setting the pressure of the three pressings to rise in steps, a high-density tertiary sintered block can be obtained.

[0016] The above-mentioned method for preparing a special solder for tantalum / Q345R steel is characterized in that the concentrations of the AgNO4 solution and the Na2WO4 solution in step one are both 0.1 mol / L to 0.5 mol / L, and the molar ratio of the solute in the AgNO4 solution to the Na2WO4 solution is not greater than 2:1.

[0017] The method for preparing the above-mentioned tantalum / Q345R steel special solder is characterized in that the particle size of the Ag2WO4 powder in step 2 is not greater than 300nm.

[0018] The above-mentioned method for preparing a special solder for tantalum / Q345R steel is characterized in that the particle size of the AgCu eutectic alloy powder in step three is 5μm~20μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 0.5μm~3μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 1μm~5μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 1μm~5μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 1μm~5μm, and the mass purity is not less than 99.9%, and the particle size of the Ce powder is 1μm~5μm, and the mass purity is not less than 99.9%.

[0019] The method for preparing the above-mentioned tantalum / Q345R steel special solder is characterized in that the heating rates in step four, step five, step six and step seven are all 5°C / min to 10°C / min.

[0020] The present invention is used to ensure uniform temperature inside and outside the material by controlling the heating rate.

[0021] The method for preparing the above-mentioned tantalum / Q345R steel special solder is characterized in that the deformation amount of the one-time rolling in step seven is 30% to 70%.

[0022] In addition, the present invention discloses a brazing process of the above-mentioned tantalum / Q345R steel special brazing filler metal, characterized in that the brazing process comprises the following steps:

[0023] Step 1: Grind the tantalum / Q345R steel special brazing filler metal and lay it between tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, and fix it to obtain the component to be brazed;

[0024] Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature is raised to 600℃~670℃ and kept warm, then raised to 750℃~850℃ and kept warm, and finally cooled with the furnace.

[0025] The above-mentioned brazing process is characterized in that the fixing method described in step one is: the edges and end points of the tantalum / AgCu-based solder / Q345R steel structure component are fixed with a clamp, and a pressure of 1kPa to 3kPa is applied to the top center of the tantalum / AgCu-based solder / Q345R steel structure component.

[0026] The present invention can ensure uniform thickness of the weld by fixing the edges and end points of the tantalum / AgCu-based solder / Q345R steel structure component and applying pressure to the center, thereby avoiding welding defects caused by edge warping and improving the mechanical properties of the weld.

[0027] The brazing process is characterized in that the heating rate in step 2 is 5°C / min to 15°C / min, and the cooling rate is 3°C / min to 5°C / min.

[0028] The invention is used to prevent the weld from generating internal stress and thermal cracks by controlling the cooling rate.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. The present invention uses AgCu eutectic as a matrix to reduce the melting point of solder, avoid the degradation of Q235 steel performance due to excessively high soldering temperature, and uses Ni, Sn, Ti, In, Ce and Ag2WO4 to coordinately regulate the performance of AgCu eutectic; wherein, the addition of Ti element can react with Ta element to form a good connection, but it is easy to generate a brittle phase, and the addition of Ni element can inhibit the generation of brittle phase and effectively refine the solder structure, and Ni element can also react with Ta element, and the combination of the two can enhance plasticity, improve joint bonding strength, corrosion resistance and high temperature performance. However, too much Ni and Ti elements will increase the solid-liquid phase temperature of the solder, so adding Sn and In elements can appropriately reduce the melting point of the solder, and can also regulate the weld structure and improve the uniformity of the weld structure; by adding Ce element and Ag2WO4, the phase interface can be further regulated to improve the spreading wettability of the solder. Through the combined effect of the above elements and components, a brazing filler metal suitable for brazing tantalum and Q345R steel can be obtained, avoiding the complex welding process, high cost and damage to the environment caused by explosive welding.

[0031] 2. The preparation method of the present invention generates small-sized Ag2WO4 by adding Na2WO4 solution while stirring AgNO4 solution, which can coat other phase particles and melt and flow during the sintering process, which is helpful to regulate the solder structure and wettability. At the same time, since the melting point of Ag2WO4 is about 600℃~650℃, the temperature is first raised to 600℃~670℃ during the brazing process to keep it warm, so that Ag2WO4 is melted first, which is beneficial to improve the spreading wettability of the solder and reduce weld defects.

[0032] 3. The preparation method of the solder of the present invention adopts three-dimensional oscillation powder mixing to maximize the uniformity of the components in the solder, avoiding the difference in specific gravity and particle size of each powder particle during the initial stirring process, which leads to different sedimentation rates and further limits the uniformity of powder in some areas; then, by performing three pressing and sintering, the solder can be continuously shrunk, the gas content inside the solder can be reduced, the machinability of the solder during rolling can be improved, and it can be ensured that there is no swelling problem after rolling and annealing.

[0033] 4. The solder composition prepared by the present invention is easy to control, has no segregation problem, and has good processing performance and welding performance.

[0034] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the metallographic structure diagram of the tantalum / Q345R steel special solder obtained in Example 1 of the present invention.

[0036] Figure 2This is the metallographic structure diagram of the tantalum / Q345R steel weld obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0037] Example 1

[0038] The solder of this embodiment is composed of the following components in mass percentage: Ni 2%, Sn 2%, In 2%, Ti 5%, Ag2WO41%, Ce 1%, and the balance is AgCu eutectic; the preparation method of the solder comprises the following steps:

[0039] Step 1, adding a 0.1 mol / L Na2WO4 solution during the stirring of a 0.1 mol / L AgNO4 solution to obtain a precipitation suspension; the molar ratio of the solute in the AgNO4 solution to that in the Na2WO4 solution is not greater than 2:1;

[0040] Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder with a particle size of 300 nm;

[0041] Step 3: According to the composition of the target solder, weigh AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder, Ce powder and the Ag2WO4 powder obtained in step 2, mix them with anhydrous ethanol, perform ultrasonic stirring, and then heat and stir until the anhydrous ethanol is completely volatilized, and then perform three-dimensional oscillation mixing to obtain a composite powder; the particle size of the AgCu eutectic alloy powder is 20μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 3μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 5μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 5μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 5μm, and the mass purity is not less than 99.9%, and the particle size of the Ce powder is 5μm, and the mass purity is not less than 99.9%;

[0042] Step 4: Place the composite powder obtained in step 3 into a mold and press it at a pressure of 150 MPa for 2 minutes, then press it at a vacuum degree of less than 10 -3 Pa, the temperature was raised to 700°C at a rate of 10°C / min for primary vacuum sintering for 2h to obtain a primary sintered block;

[0043] Step 5: The primary sintered block obtained in step 4 is pressed into shape at a pressure of 300 MPa for 2 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 700°C at a rate of 10°C / min for secondary vacuum sintering for 2h to obtain a secondary sintered block;

[0044] Step 6: The secondary sintered block obtained in step 5 is pressed into shape at a pressure of 850 MPa for 2 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 650°C at a rate of 10°C / min and vacuum sintered for 1 h three times to obtain a three-sintered block;

[0045] Step 7: The tertiary sintered block obtained in step 6 is rolled once using a double-roll rolling mill with a deformation amount of 30% to 70%, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 700°C at a rate of 10°C / min and then annealed for 2h, and the process of rolling followed by annealing was repeated until the thickness of the sintered block was no more than 200μm to obtain a special brazing filler metal for tantalum / Q345R steel.

[0046] The metallographic structure of the tantalum / Q345R steel special brazing filler metal obtained in this embodiment was analyzed. Figure 1 As shown, the solder exhibits obvious Ag-Cu eutectic, indicating that the components of the solder are fully fused and no defects such as pores occur.

[0047] The brazing process using the above-mentioned brazing material comprises the following steps:

[0048] Step 1: Grind the tantalum / Q345R steel special brazing filler metal to 100 μm and then lay it between the tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, fix the edges and end points of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component with a clamp, and apply a pressure of 1 kPa at the top center of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component to obtain a component to be brazed;

[0049] Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature was raised to 600°C at a rate of 5°C / min and kept for 10 min, then raised to 850°C at a rate of 5°C / min and kept for 20 min, and finally cooled with the furnace at a rate of 3°C / min to 5°C / min to obtain a tantalum / Q345R steel weld.

[0050] Example 2

[0051] The solder of this embodiment is composed of the following components in mass percentage: Ni 5%, Sn 5%, In 5%, Ti 3%, Ag2WO42%, Ce 1%, and the balance is AgCu eutectic; the preparation method of the solder comprises the following steps:

[0052] Step 1, adding a 0.3 mol / L Na2WO4 solution during the stirring of a 0.3 mol / L AgNO4 solution to obtain a precipitation suspension; the molar ratio of the solute in the AgNO4 solution to that in the Na2WO4 solution is not greater than 2:1;

[0053] Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder with a particle size of 200 nm;

[0054] Step 3, according to the composition of the target solder, weigh AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder, Ce powder and the Ag2WO4 powder obtained in step 2, mix them with anhydrous ethanol, perform ultrasonic stirring, and then heat and stir until the anhydrous ethanol is completely volatilized, and then perform three-dimensional oscillation mixing to obtain a composite powder; the particle size of the AgCu eutectic alloy powder is 5μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 0.5μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 1μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 1μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 1μm, and the mass purity is not less than 99.9%, and the particle size of the Ce powder is 1μm, and the mass purity is not less than 99.9%;

[0055] Step 4: Place the composite powder obtained in step 3 into a mold and press it at a pressure of 50 MPa for 5 minutes, then place the mold under a vacuum of less than 10 -3 Pa, the temperature was raised to 600°C at a rate of 5°C / min for primary vacuum sintering for 3h to obtain a primary sintered block;

[0056] Step 5: The primary sintered block obtained in step 4 is pressed into shape at a pressure of 150 MPa for 5 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 600°C at a rate of 5°C / min for secondary vacuum sintering for 3h to obtain a secondary sintered block;

[0057] Step 6: The secondary sintered block obtained in step 5 is pressed into shape at a pressure of 850 MPa for 5 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 550°C at a rate of 5°C / min and vacuum sintered for three times for 2 h to obtain a three-time sintered block;

[0058] Step 7: The tertiary sintered block obtained in step 6 is rolled once using a double-roll rolling mill with a deformation amount of 30% to 70%, and then the vacuum degree is less than 10 -3Pa, the temperature was raised to 600°C at a rate of 5°C / min and then annealed for 3h. The process of rolling followed by annealing was repeated until the thickness of the sintered block was no more than 200μm to obtain a special brazing filler metal for tantalum / Q345R steel.

[0059] The brazing process using the above-mentioned brazing material comprises the following steps:

[0060] Step 1: Grind the tantalum / Q345R steel special brazing filler metal to 80 μm and then lay it between the tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, fix the edges and end points of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component with a clamp, and apply a pressure of 2 kPa at the top center of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component to obtain a component to be brazed;

[0061] Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature was increased to 600°C at a rate of 10°C / min and kept for 10 min, then increased to 750°C at a rate of 10°C / min and kept for 15 min, and finally cooled with the furnace at a rate of 3°C / min to 5°C / min to obtain a tantalum / Q345R steel weld.

[0062] Example 3

[0063] The solder of this embodiment is composed of the following components in mass percentage: Ni 3%, Sn 4%, In 3%, Ti 1%, Ag2WO42%, and the balance is AgCu eutectic; the preparation method of the solder comprises the following steps:

[0064] Step 1, adding a 0.2 mol / L Na2WO4 solution during the stirring of a 0.2 mol / L AgNO4 solution to obtain a precipitation suspension; the molar ratio of the solute in the AgNO4 solution to that in the Na2WO4 solution is not greater than 2:1;

[0065] Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder with a particle size of 260 nm;

[0066] Step 3: According to the composition of the target solder, weigh AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder, Ce powder and the Ag2WO4 powder obtained in step 2, mix them with anhydrous ethanol, perform ultrasonic stirring, and then heat and stir until the anhydrous ethanol is completely volatilized, and then perform three-dimensional oscillation mixing to obtain a composite powder; the particle size of the AgCu eutectic alloy powder is 8μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 1μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 2μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 2μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 2μm, and the mass purity is not less than 99.9%;

[0067] Step 4: Place the composite powder obtained in step 3 into a mold and press it at a pressure of 100 MPa for 3 minutes, then press it at a vacuum degree of less than 10 -3 Pa, the temperature was raised to 650°C at a rate of 8°C / min for primary vacuum sintering for 3h to obtain a primary sintered block;

[0068] Step 5: The primary sintered block obtained in step 4 is pressed into shape at a pressure of 200 MPa for 3 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 650°C at a rate of 8°C / min for secondary vacuum sintering for 3h to obtain a secondary sintered block;

[0069] Step 6: The secondary sintered block obtained in step 5 is pressed into shape at a pressure of 850 MPa for 3 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 650°C at a rate of 8°C / min and vacuum sintered for three times for 3 h to obtain a three-time sintered block;

[0070] Step 7: The tertiary sintered block obtained in step 6 is rolled once using a double-roll rolling mill with a deformation amount of 30% to 70%, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 650°C at a rate of 8°C / min and then annealed for 3h. The process of rolling followed by annealing was repeated until the thickness of the sintered block was no more than 200μm to obtain a special brazing filler metal for tantalum / Q345R steel.

[0071] The brazing process using the above-mentioned brazing material comprises the following steps:

[0072] Step 1: Grind the tantalum / Q345R steel special brazing filler metal to 80 μm and then lay it between the tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, fix the edges and end points of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component with a clamp, and apply a pressure of 3 kPa at the top center of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component to obtain a component to be brazed;

[0073] Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature was increased to 600°C at a rate of 15°C / min and kept for 10 min, then increased to 800°C at a rate of 15°C / min and kept for 18 min, and finally cooled with the furnace at a rate of 3°C / min to 5°C / min to obtain a tantalum / Q345R steel weld.

[0074] The metallographic structure of the tantalum / Q345R steel weld obtained in this embodiment was analyzed. Figure 2 As shown, the weld and the base materials on both sides show obvious transition layers, indicating that obvious atomic diffusion occurs at the interface and the welding quality is good.

[0075] Example 4

[0076] The solder of this embodiment is composed of the following components in mass percentage: Ni 4%, Sn 4%, In 3%, Ti 2%, Ag2WO4 2%, Ce 1%, and the balance is AgCu eutectic; the preparation method of the solder comprises the following steps:

[0077] Step 1, adding a 0.5 mol / L Na2WO4 solution during the stirring of a 0.5 mol / L AgNO4 solution to obtain a precipitation suspension; the molar ratio of the solute in the AgNO4 solution to that in the Na2WO4 solution is not greater than 2:1;

[0078] Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder with a particle size of 100 nm;

[0079] Step 3, according to the composition of the target solder, weigh AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder, Ce powder and the Ag2WO4 powder obtained in step 2, mix them with anhydrous ethanol, perform ultrasonic stirring, and then heat and stir until the anhydrous ethanol is completely volatilized, and then perform three-dimensional oscillation mixing to obtain a composite powder; the particle size of the AgCu eutectic alloy powder is 12μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 1μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 2μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 2μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 2μm, and the mass purity is not less than 99.9%, and the particle size of the Ce powder is 2μm, and the mass purity is not less than 99.9%;

[0080] Step 4: Place the composite powder obtained in step 3 into a mold and press it at a pressure of 50 MPa for 5 minutes, then place the mold under a vacuum of less than 10 -3 Pa, the temperature was raised to 670°C at a rate of 5°C / min for primary vacuum sintering for 3h to obtain a primary sintered block;

[0081] Step 5: The primary sintered block obtained in step 4 is pressed into shape at a pressure of 150 MPa for 5 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 670°C at a rate of 5°C / min for secondary vacuum sintering for 3h to obtain a secondary sintered block;

[0082] Step 6: The secondary sintered block obtained in step 5 is pressed into shape at a pressure of 850 MPa for 5 minutes, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 620°C at a rate of 5°C / min and vacuum sintered for three times for 2 h to obtain a three-time sintered block;

[0083] Step 7: The tertiary sintered block obtained in step 6 is rolled once using a double-roll rolling mill with a deformation amount of 30% to 70%, and then the vacuum degree is less than 10 -3 Pa, the temperature was raised to 600°C at a rate of 5°C / min and then annealed for 3h. The process of rolling followed by annealing was repeated until the thickness of the sintered block was no more than 200μm to obtain a special brazing filler metal for tantalum / Q345R steel.

[0084] The brazing process using the above-mentioned brazing material comprises the following steps:

[0085] Step 1: Grind the tantalum / Q345R steel special brazing filler metal to 100 μm and then lay it between the tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, fix the edges and end points of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component with a clamp, and apply a pressure of 2 kPa at the top center of the tantalum / AgCu-based brazing filler metal / Q345R steel structural component to obtain a component to be brazed;

[0086] Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature was raised to 670°C at a rate of 15°C / min and kept for 10 min, then raised to 820°C at a rate of 15°C / min and kept for 18 min, and finally cooled with the furnace at a rate of 3°C / min to 5°C / min to obtain a tantalum / Q345R steel weld.

[0087] The tantalum / Q345R steel welds obtained in Examples 1 to 4 were subjected to shear strength tests. The results are shown in Table 1.

[0088] Table 1 Shear strength of tantalum / Q345R steel welds in Examples 1 to 4

[0089] sample Weld strength / MPa Example 1 145.6 Example 2 178.4 Example 3 163.3 Example 4 154.5

[0090] As can be seen from Table 1, the shear strength of the tantalum / Q345R steel welds obtained in Examples 1 to 4 are all greater than 140 MPa, indicating that the brazing material and brazing process of the present invention can effectively connect tantalum and Q345R steel.

[0091] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A tantalum / Q345R steel special brazing filler metal, characterized in that: The solder consists of the following components in percentage by mass: Ni 2% to 5%, Sn 2% to 5%, In 2% to 5%, Ti 1% to 5%, Ag2WO4 1% to 2%, Ce 0% to 1%, and the balance is AgCu eutectic.

2. A method for preparing the tantalum / Q345R steel special brazing filler metal as claimed in claim 1, characterized in that: The preparation method comprises the following steps: Step 1: adding Na2WO4 solution during the stirring process of AgNO4 solution to obtain a precipitate suspension; Step 2: Wash the precipitate suspension obtained in step 1 several times, filter and dry it to obtain Ag2WO4 powder; Step 3, the Ag2WO4 powder obtained in step 2 and the AgCu eutectic alloy powder, Ni powder, Sn powder, Ti powder, In powder and Ce powder are mixed with anhydrous ethanol and ultrasonically stirred, and then heated and stirred until the anhydrous ethanol is completely volatilized and then three-dimensionally shaken and mixed to obtain a composite powder; Step 4: Put the composite powder obtained in step 3 into a mold and press it under a pressure of 50MPa to 150MPa, then heat it to 600°C to 700°C for primary vacuum sintering to obtain a primary sintered block; Step 5: Pressing the primary sintered block obtained in step 4 under a pressure of 150 MPa to 300 MPa, and then heating to 600° C. to 700° C. for secondary vacuum sintering to obtain a secondary sintered block; Step 6: Press the secondary sintered block obtained in step 5 under a pressure of 850 MPa or more, and then heat it to 550° C. to 650° C. for a third vacuum sintering to obtain a third sintered block; Step seven, rolling the tertiary sintered block obtained in step six, then heating it to 600°C to 700°C and annealing it, repeating the process of first rolling and then annealing until the thickness of the tertiary sintered block is not more than 200 μm, and obtaining a special brazing material for tantalum / Q345R steel.

3. The method for preparing a tantalum / Q345R steel special brazing filler metal according to claim 2, characterized in that: The concentrations of the AgNO4 solution and the Na2WO4 solution in step 1 are both 0.1 mol / L to 0.5 mol / L, and the molar ratio of the solute in the AgNO4 solution to the Na2WO4 solution is not greater than 2:

1.

4. The method for preparing a tantalum / Q345R steel special brazing filler metal according to claim 2, characterized in that: The particle size of the Ag2WO4 powder in step 2 is not greater than 300 nm.

5. The method for preparing a tantalum / Q345R steel special brazing filler metal according to claim 2, characterized in that: The particle size of the AgCu eutectic alloy powder in step three is 5μm~20μm, and the mass purity is not less than 99.9%; the particle size of the Ni powder is 0.5μm~3μm, and the mass purity is not less than 99.9%; the particle size of the Sn powder is 1μm~5μm, and the mass purity is not less than 99.9%; the particle size of the Ti powder is 1μm~5μm, and the mass purity is not less than 99.9%; the particle size of the In powder is 1μm~5μm, and the mass purity is not less than 99.9%, and the particle size of the Ce powder is 1μm~5μm, and the mass purity is not less than 99.9%.

6. The method for preparing a tantalum / Q345R steel special brazing filler metal according to claim 2, characterized in that: The heating rates in step 4, step 5, step 6 and step 7 are all 5°C / min to 10°C / min.

7. The method for preparing a tantalum / Q345R steel special brazing filler metal according to claim 2, characterized in that: The deformation amount of the first rolling in step seven is 30% to 70%.

8. A brazing process using the tantalum / Q345R steel special brazing filler metal as claimed in claim 1, characterized in that: The brazing process includes the following steps: Step 1: Grind the tantalum / Q345R steel special brazing filler metal and lay it between tantalum and Q345R steel to form a tantalum / AgCu-based brazing filler metal / Q345R steel structural component, and fix it to obtain the component to be brazed; Step 2: Place the components to be brazed obtained in step 1 in a vacuum brazing furnace and evacuate to 5×10 -3 After Pa, the temperature is raised to 600℃~670℃ and kept warm, then raised to 750℃~850℃ and kept warm, and finally cooled with the furnace.

9. The brazing process according to claim 8, characterized in that: The fixing method described in step 1 is: fix the edges and end points of the tantalum / AgCu-based solder / Q345R steel structure component with a clamp, and apply a pressure of 1kPa to 3kPa at the top center of the tantalum / AgCu-based solder / Q345R steel structure component.

10. The brazing process according to claim 8, characterized in that: The heating rate in step 2 is 5°C / min to 15°C / min, and the cooling rate is 3°C / min to 5°C / min.

Citation Information

Patent Citations

  • Platinum-tantalum-platinum three-layer composite screen and method for producing the same

    CN101429663A

  • Medium-temperature zinc-based brazing filler metal for brazing copper and steel and preparation method thereof

    CN102500949A

  • Cadmium-free silver-based solder used for titanium / steel dissimilar alloy TIG welding-brazing

    CN104191105A

  • Amorphous high-entropy alloy solder for braze-welding tantalum and steel and preparation method

    CN104480412A

  • Intermediate layer alloy applied to resistance spot-welding of tantalum Ta1 and Q235 and preparation method thereof

    CN109202244A